The Support Paradox in Community Enterprise Experiments in The Netherlands - Reinout Kleinhans; Maarten van Ham (Institute for the Study of Labor (IZA), 2016)
In many European countries, community entrepreneurship is increasingly considered as a means to initiate small-scale urban regeneration. However, residents in deprived communities are often viewed to lack key entrepreneurial attributes and skills. This paper reports a unique experiment in the Netherlands with nascent community enterprises which received start-up support from a private foundation. This paper investigates how active citizens perceive the benefits and drawbacks of this support. In depth analysis of transcriptions of repeated semi-structured interviews (panel design with the same respondents) with representatives of established community enterprises and resident groups were analysed. While we find positive feedback on provided support, our research provides strong evidence for a 'support paradox': the support that was intended to overcome a number of entry barriers and difficulties on the road to community entrepreneurship has in fact significantly hampered progress among several of the studied CEs.
Keywords: D71; L26; L31; O35; R23; 330; community enterprises; community entrepreneurship; active citizenship; support; urban regeneration; self-organisation; The Netherlands